Academic outcomes and accommodations following adolescent sport-related concussion: a pilot study - Kelly Russell; Erin Selci; Stephanie Chu; Adrian Rozbacher; Michael Ellis (Concussion, 2017)
Aim: The purpose of this study was to examine academic achievement, absenteeism and school accommodations following adolescent sport-related concussion (SRC). Methods: A case-series was conducted a...